A Method for Solving the Voltage and Torque Equations of the Split-Phase Induction Machines - G. A. Olarinoye; J. Y. Oricha (Nigerian Journal of Technological Development, 2013)
Single phase induction machines have been the subject of many researches in recent times. The voltage and torque equations which describe the dynamic characteristics of these machines have been quoted in many papers, including the papers that present the simulation results of these model equations. The way and manner in which these equations are solved is not common in literature. This paper presents a detailed procedure of how these equations are to be solved with respect to the splitphase induction machine which is one of the different types of the single phase induction machines available in the market. In addition, these equations have been used to simulate the start-up response of the split phase induction motor on no-load. The free acceleration characteristics of the motor voltages, currents and electromagnetic torque have been plotted and discussed. The simulation results presented include the instantaneous torque-speed characteristics of the Split phase Induction machine. A block diagram of the method for the solution of the machine equations has also been presented.